Pigs as a potential source of emerging livestock-associated Staphylococcus aureus in Africa: a systematic review. (August 2021) - Samutela, Mulemba Tillika; Kwenda, Geoffrey; Simulundu, Edgar; Nkhoma, Panji; Higashi, Hideaki; Frey, Andrew; Bates, Matthew; Hang'ombe, Bernard M.
Highlights: Staphylococcus aureus including methicillin-resistant S. aureus (MRSA) are prevalent in African pig and pork production systems. The presence of antimicrobial, heavy metal resistance and virulence factor genes was noted. The typical ST398 MRSA strains among pigs have been reported in Africa. Other detected genotypes suggest an anthropogenic origin rather than zoonosis. ABSTRACT: Objective: To assess the emergence of livestock-associated Staphylococcus aureus including methicillin-resistant S. aureus (MRSA) in the pig and pork production systems in Africa for the past two decades. Methods: PubMed and African Journals OnLine were searched for relevant primary studies from 2000 to 2019 using standardized key words. In total, 19 eligible articles were included in this review. Results: The prevalence of S. aureus including MRSA ranged from 0% to 55% among live pigs and raw pork, and from 9.4% to 30.8% among pig farm and abattoir workers. Risk factors associated with S. aureus carriage among workers were: male gender, working in an abattoir, and medical-related occupation of a household member. S. aureus and MRSA from pigs and pork production systems in Africa are potentially pathogenic with diverse spa types and clonal complexes, with genes encoding antimicrobial resistance, heavy metal resistance, and virulence factors including secreted and enterotoxins, proteases and immune evasion cluster. The typical livestock-associated S. aureus CC398 and mecC genes were reported in two studies. Conclusion: Pigs are a potential source of the emerging livestock-associated S. aureus in Africa. Continued monitoring using a 'One Health' approach is recommended for effective infection prevention and control of these infections in Africa.